Quantitative analysis of toughening effect of crack deflection on Si3N4/Si2N2O composites through improved indentation method. Issue 2 (1st February 2018) - Luo, Junting; Luo, Shuyi; Gu, Yongfei; Zhang, Lili; Zhang, Chunxiang; Xue, Yahong; Zhang, Zhen
Abstract: In this study, Si3 N4 /Si2 N2 O composite ceramics prepared by hot pressing were used as an example, and the material fracture morphology and fracture mechanism were analyzed. Based on the formula of fracture toughness measured by an indentation method, a quantitative computation method was proposed to determine the toughened effect of ceramic materials resulting from the crack deflection by the second phase. The grain size and sintering density are increased with the increase of sintering temperature. The toughening effects resulting from the crack deflection is increased, and the main mode of fracture is transformed into the transgranular fracture. The Si2 N2 O grains can play a role in the toughening process because these grains can hinder the cracks extending along the radial direction. However, when the cracks extend in the axial direction, the toughening effect of Si2 N2 O grains is not obvious because of the internal stacking faults in the axial direction. The improved indentation method can quantitatively analyze the toughening effect of the second phase of composite ceramics, and the validity of this method are verified by comparing the fracture toughness of Si3 N4/Si2 N2 O and fine grained β- Si3 N4 ceramics.